2017
DOI: 10.1371/journal.pone.0187408
|View full text |Cite
|
Sign up to set email alerts
|

A glimpse at the intricate mosaic of ethnicities from Mesopotamia: Paternal lineages of the Northern Iraqi Arabs, Kurds, Syriacs, Turkmens and Yazidis

Abstract: Widely considered as one of the cradles of human civilization, Mesopotamia is largely situated in the Republic of Iraq, which is also the birthplace of the Sumerian, Akkadian, Assyrian and Babylonian civilizations. These lands were subsequently ruled by the Persians, Greeks, Romans, Arabs, Mongolians, Ottomans and finally British prior to the independence. As a direct consequence of this rich history, the contemporary Iraqi population comprises a true mosaic of different ethnicities, which includes Arabs, Kurd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 41 publications
(51 reference statements)
3
31
0
Order By: Relevance
“…Typing method: ThermoFisher Precision ID Ancestry panel a Indicates population samples and SNP data reported for first time in this study b Indicates population samples reported initially in a previous publication as cited here in the data source column of this table. SNP data in this study was supplied by co-authors; see footnote #4 c Indicates SNP data and population samples employed in this study that derive from publications as cited here in data source column of this table d Indicates population samples initially reported in a previous publication [13] for Y-chromosome data only. The autosomal SNP data in this study has not been reported previously…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Typing method: ThermoFisher Precision ID Ancestry panel a Indicates population samples and SNP data reported for first time in this study b Indicates population samples reported initially in a previous publication as cited here in the data source column of this table. SNP data in this study was supplied by co-authors; see footnote #4 c Indicates SNP data and population samples employed in this study that derive from publications as cited here in data source column of this table d Indicates population samples initially reported in a previous publication [13] for Y-chromosome data only. The autosomal SNP data in this study has not been reported previously…”
Section: Methodsmentioning
confidence: 99%
“…d Indicates population samples initially reported in a previous publication [13] for Y-chromosome data only. The autosomal SNP data in this study has not been reported previously…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Y chromosomal haplogroups can be assigned from Y-STR haplotypes using haplogroup predictors, which are very useful for analysing previous published Y-STR datasets (Dogan et al 2016;Dogan et al 2017;Heraclides et al 2017;Gurkan et al 2017) as well as validation purposes of haplogroup assignments based on Y SNP data (Petrejčíková et al 2014 andEmmerova et al 2017). The four haplogroup predictors that are in focus in this study are: Whit Athey haplogroup predictor (Athey 2006), Nevgen haplogroup predictor (Ćetković -Gentula and Nevski 2015), Vadim Urasin's…”
Section: Introductionmentioning
confidence: 99%